Model Pendampingan Berbasis Manajemen Pendidikan Islam Terhadap Transformasi Digital Pemasaran UMKM di Kampung Pitara - Basori, Ahmad; Agustin, Melani Putri; Priadi, Rapi; Septiani, Armenia (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2026)
This community service activity aims to outline the knowledge transfer process within the Islamic Education Management (IEM) framework through digital marketing assistance for starfruit MSMEs in Pitara Village, Pancoran Mas. IEM encompasses community-based education management as a strategy for empowering the community. Partners face an imbalance between production capacity and traditional marketing systems, resulting in suboptimal economic value-added potential. The program was implemented using a participatory approach through planning, product quality improvement education, digital mentoring, and evaluation of changes in business behavior. The results demonstrate a shift to digital marketing management, with the strengthening of product visual identity and the use of TikTok Affiliates, expanding the market and increasing transactions. Furthermore, there has been a shift in the mindset of human resources, from simply selling products to managing more systematic marketing strategies. In MPI's perspective, students and colleges function as education managers as well as agents of change who manage the process of education and the transformation of society's behavior in a structured, planned, and oriented towards strengthening economic independence. This program affirms that the synergy between education management and digital literacy is a strategic instrument in the empowerment of UMKM based on Islamic values ​​that are innovative and responsive to the dynamics of the digital economy.